Effect of Sintering Temperature on the Phase Formation and Superconducting Properties of Bi1.6Pb0.4Sr2Ca2Cu3O10 Ceramics Synthesised via Co-Precipitation - Hapipi, Nurhidayah Mohd; Chen, Soo Kien; Kechik, Mohd Mustafa Awang; Lim, Kean Pah; Shaari, Abdul Halim; Baharuddin, Nor Atikah; Khalid, Nurul Auni; Shabdin, Muhammad Kashfi; Tan, Kar Ban; Lee, Oon Jew (Journal of Material Science and Radiation, 2025)
In this work, (Bi, Pb)-2223 superconducting ceramics with the nominal composition Bi1.6Pb0.4Sr2Ca2Cu3O10 were synthesised via the co-precipitation method and sintered at temperatures of 845 °C, 850 °C, and 855 °C. X-ray diffraction (XRD) analysis confirmed the dominance of Bi1.6Pb0.4Sr2Ca2Cu3O10 phase with minor traces of secondary phases, Ca2PbO4 (dicalcium lead (IV) oxide). An increase in sintering temperature led to a larger average grain size and reduced intergranular voids. Electrical resistivity measurements using the four-point probe method revealed the highest superconducting transition temperature (Tc onset = 104 K) for samples sintered at 845 °C. Higher sintering temperatures reduced the value of Tc onset and resulted in a wider transition width, ΔTc. These findings highlight the critical influence of sintering temperature on the structural and microstructural properties, which in turn govern the superconducting performance of (Bi, Pb)-2223 ceramics.